Analisis Yuridis terhadap Perjanjian Kerja Waktu Tertentu (PKWT) dalam Hubungan Kerja (Studi Kasus pada PT. Gratia Jaya Farma) - Dilaga, Daniel Dikya; Saputra, Arikha (Universitas Batanghari Jambi, 2024)
The demographic bonus period in Indonesia has an impact on the availability of workers of productive age for companies. The weak position of workers in employment relations means that many workers do not get their rights as they should. In this case, the working relationship between PT. Gratia Jaya Farma and its employees who use a Specific Time Work Agreement (PKWT) should be based on the laws governing employment in Indonesia. Thus, this research aims to explain more specifically the contractual relationship in the implementation of a Specific Time Work Agreement (PKWT) at PT. Gratia Jaya Farma from a positive legal perspective. The type of research used is sociological juridical with qualitative analysis techniques. This research was carried out at PT. Gratia Jaya Farma, with data sources in the form of interviews with relevant informants and secondary data in the form of literature reviews, journals and other documents. The results of the research show that the implementation of the Specific Time Work Agreement (PKWT) at PT. Gratia Jaya Farma is largely in line with Government Regulation Number 35 of 2021 and other provisions. Things that are implemented include the terms and conditions for the validity of the work agreement, the nature and type of work, the rights and obligations of the parties and so on. Meanwhile, provisions that have not been implemented and inhibiting factors must be evaluated in order to create a good working relationship.